Mobility enhancement of CVD graphene by spatially correlated charges - Turyanska, Lyudmila; Makarovsky, Oleg; Eaves, Laurence; Patanè, Amalia; Mori, N. (IOP Publishing, 2017)
The manuscript presents a strategy for enhancing the carrier mobility of single layer CVD graphene (CVD SLG) based on spatially correlated charges. Our Monte Carlo simulations, numerical modeling and the experimental results confirm that spatial correlation between defects with opposite charges can provide a means to control independently the carrier concentration and mobility of planar field effect transistors in which graphene is decorated with a layer of colloidal quantum dots (QDs). We show that the spatial correlation between electrically charged scattering centres close to the graphene/SiO2 interface and the localised charges in a QD layer can smooth out the electrostatic potential landscape, thus reducing scattering and enhancing the carrier mobility. The QD capping molecules influence the distribution and correlation of electrical charges in the vicinity of SLG and provide a means of tuning the carrier concentration and increasing the carrier mobility in graphene. These results represent a significant conceptual advance and provide a novel strategy for control of the electronic properties of 2D materials that could accelerate their utilization in optoelectronic devices.